2004
DOI: 10.1029/2004ja010487
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of Schumann resonance frequency in NS and EW magnetic components

Abstract: [1] The diurnal variation of the frequency of the first Schumann resonance mode has been studied from three ELF observation sites located at Spitsbergen, the Kola Peninsula, and the Kamchatka Peninsula. The induction magnetometer measured ELF separately in two components: NS (north-south) and EW (east-west). The frequency variation is 0.2-0.3 Hz at all the observatories. The semidiurnal harmonics dominate in the frequency variation. The variation seems to be controlled by the local time (LT) rather than by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
0
17
0
2
Order By: Relevance
“…[21] Roldugin et al [2004b] concluded that diurnal SR frequency variation is mainly controlled by local time, and the different field components undergo different variation patterns because of the horizontal inhomogeneity of the ionosphere. Nickolaenko et al [1998] found that the source area of the global lightning activity also plays an important role affecting the SR frequency variation.…”
Section: Rs2s14mentioning
confidence: 99%
“…[21] Roldugin et al [2004b] concluded that diurnal SR frequency variation is mainly controlled by local time, and the different field components undergo different variation patterns because of the horizontal inhomogeneity of the ionosphere. Nickolaenko et al [1998] found that the source area of the global lightning activity also plays an important role affecting the SR frequency variation.…”
Section: Rs2s14mentioning
confidence: 99%
“…The changes in SR frequencies are sensitive to a general increase/decrease of conductivity within the outer layer (Sátori et al, 2005). It has been found, experimentally, that the variations in the N-S and E-W magnetic components occur in antiphase for the first Schumann resonance frequency (Roldugin et al, 2004a). Sátori (1996) studied that the average daily frequency patterns are different for the three modes.…”
Section: R Chand Et Al: Schumann Resonance Frequency Variations Obsmentioning
confidence: 99%
“…Roldugin et al (1999) showed that the SR frequency depends both on the electron density in the ionospheric Dregion and on the base height of this region. For the interpretation of our data, we now consider, in some detail, the simple model of Roldugin et al (2003), for which the authors establish a quantitative relation between SR frequencies and the ionospheric parameters. Considered is a two-layer model, where the discontinuous relative electrical permittivity assumes the values [taking z from the Earth's surface positive upwards and assuming a time factor exp (iωt)]…”
Section: Estimation Of Electron Density In Lower Ionospherementioning
confidence: 99%
See 2 more Smart Citations